The Europeanization of Regions in Eastern and Western Europe. Theoretical Perspectives - Sturm, Roland; Dieringer, Jürgen (Regional and federal studies, 2005)
Today we witness the process of Europeanization of subnational regions in the 2004 pre-enlargement EU countries and in the new member states. This article reflects on our knowledge about this phenomenon, especially with regard to an East - West comparison. It asks: which promising theoretical approaches have been developed so far for the analysis of (a) the institutional options the Europeanization process provides for the regions and (b) the Europeanization of policy-making in the regions. It points outs that current research is in danger of overestimating formal institutional convergence when comparing the Europeanization of regions, and of underestimating and/or overlooking the consequences of institutional reform for the future fabric of societies and regional political exchange. For the Europeanization of regional policy-making as well as for the impact of Europeanization on regional societies a theoretical framework is developed here. © 2005 Taylor & Francis Group Ltd.
UnivIS-Import:2015-03-09:Pub.2005.phil.dsp.ipowi.lpowi1.theeur
Keywords: Accession countries; Europeanization; Institutions; Policy-making; Regionalization